2009
DOI: 10.1007/s00436-009-1474-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of hard and soft ticks from Romania by sequences of the internal transcribed spacers of ribosomal DNA

Abstract: In the present study, four hard tick species and one soft tick species, namely, Dermacentor marginatus, Haemaphysalis punctata, Haemaphysalis parva, Ixodes ricinus, and Dermanyssus gallinae, from south-western Romania were characterized genetically by the first (ITS-1) and second (ITS-2) internal transcribed spacers (ITS) of nuclear ribosomal DNA (rDNA), using a hard tick, Haemaphysalis longicornis, from China for comparative purposes. The ITS rDNA was amplified by polymerase chain reaction (PCR) and sequenced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 19 publications
3
14
0
Order By: Relevance
“…In addition, based on the comparison of morphological characteristics and examination of the syntype series of D. niveus, it was concluded that D. niveus is conspeci c with D. marginatus [13]. Also the molecular results obtained from the current study revealed a high similarity (> 98%) between D. marginatus and D. niveus based on the different populations of both species across this study and other sequences obtained from Iran [16] or elsewhere [25] ( Fig. 2).…”
Section: Discussionsupporting
confidence: 63%
“…In addition, based on the comparison of morphological characteristics and examination of the syntype series of D. niveus, it was concluded that D. niveus is conspeci c with D. marginatus [13]. Also the molecular results obtained from the current study revealed a high similarity (> 98%) between D. marginatus and D. niveus based on the different populations of both species across this study and other sequences obtained from Iran [16] or elsewhere [25] ( Fig. 2).…”
Section: Discussionsupporting
confidence: 63%
“…Total genomic DNA was isolated from individual tick using sodium dodecyl sulphate/proteinase K treatment, followed by spin-column purification (Wizard® SV Genomic DNA Purification System, Promega). The identity of these ticks were further ascertained as R. sanguineus by PCR amplification and subsequent sequencing of the region spanning the first internal transcribed spacer (ITS-1), the 5.8S and the second internal transcribed spacer (ITS-2) as reported previously 30. The ITS-2 sequence of the representative female R. sanguineus China sample (sample code FSF1) had 99.2% similarity with that of R. sanguineus from Australia (GenBank accession no.…”
Section: Methodsmentioning
confidence: 99%
“…it is relatively simple to amplify ITS rDNA by polymerase chain reaction (PCR) based on the highly conserved rDNA flanking both ITS regions (Murrell et al 2001). Furthermore, ITS rDNA has been used for the genetic characterization of ticks at inter-species and intra-species levels (McLain et al 1995;Zahler and Gothe 1997;Fukunaga et al 2000;Shaw et al 2002;Manuel et al 2007;Chitimia et al 2009). However, prior to present study, there had been no studies of ticks in China using well-defined DNA markers except the discrimination between H. qinghaiensis and H. japonica by Random Amplified Polymorphic DNA (Chang et al 2005).…”
Section: Introductionmentioning
confidence: 97%